Botulinum toxin type A reduces the expression of transient receptor potential melastatin 3 and transient receptor potential vanilloid type 4 in the trigeminal subnucleus caudalis of a rat model of trigeminal neuralgia. Issue 10 (3rd July 2019) - Zhang, Yi; Su, Qiuyang; Lian, Yajun; Chen, Yuan
Abstract : This study was designed to investigate the expression of transient receptor potential melastatin 3 (TRPM3) and transient receptor potential vanilloid type 4 (TRPV4) in the trigeminal spinal subnucleus caudalis of a rat model of trigeminal neuralgia (TN). The influence of botulinum toxin type A (BTX-A) on the expression of these channels was also explored. In this study, a model was established involving chronic constriction injury to the infraorbital nerve (ION-CCI), inducing TN. To explore the effects of BTX-A and whether it was dose related, rats were divided randomly into four groups: a control group, an ION-CCI group, a 3 U group, and a 10 U group (which received 3 and 10 U/kg BTX-A injections, respectively). Von Frey hairs were used to determine the pain threshold of the rats. The expression of TRPM3 and TRPV4 in the trigeminal spinal subnucleus caudalis was detected using western blots and immunohistochemistry. The pain thresholds of rats decreased to a minimum 14 days after ION-CCI. Compared with the ION-CCI group, the pain thresholds of the 3 and 10 U groups were significantly higher 4 days after the subcutaneous injection of BTX-A ( P <0.05). The expression of TRPM3 and TRPV4 in the ION-CCI group was significantly higher than that in the control group ( P <0.05). TRPM3 and TRPV4 expression in the 3 and 10 U groups was significantly lower than that in the ION-CCI group ( P <0.05). In conclusion, overexpression of TRPM3 and TRPV4 can jointly mediate the occurrence of mechanical hyperalgesia in TN. The analgesic effects of BTX-A may be related to the inhibition of TRPM3 and TRPV4 expression.